2014
DOI: 10.1155/2014/418085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Ranking of Organizational Resilience Factors by Using a Two-Step Fuzzy AHP and Fuzzy TOPSIS

Abstract: We presented a novel fuzzy multicriteria decision making approach to evaluate and rank organizational resilience factors with respect to user preference orders. Due to vagueness of the decision data, the precise numerical data are inadequate for real-life business situations. Human judgements can be expressed by linguistic expressions which are modeled by fuzzy sets. The complexity of the considered problem calls for analytic methods rather than intuitive decisions. Two fuzzy multi-criteria methods are propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…They proposed to evaluate internal factors (planning strategies, capability and capacity of internal resources, internal situation monitoring and reporting, human factors and quality), external factors (external situation monitoring and reporting and capability and capacity of external resources) and enabling resilience factors (design of the organization, detection potential, emergency response and safety management system). Tadić et al (2014); Macuzić et al (2016) suggested to evaluate resilience using a fuzzy approach. They suggest the following steps: (1) creating an organizational reference model and to identify the factors that contribute to resilience, (2) weighing the importance of these factors and processes using a fuzzy approach, (3) determining linguistic expressions to evaluate these factors, (4) calculating the resilience factors' values using a fuzzy approach and (5) ranking the organizational resilience factors.…”
Section: Measuring Organizational Resilience Based On Other Techniquesmentioning
confidence: 99%
“…They proposed to evaluate internal factors (planning strategies, capability and capacity of internal resources, internal situation monitoring and reporting, human factors and quality), external factors (external situation monitoring and reporting and capability and capacity of external resources) and enabling resilience factors (design of the organization, detection potential, emergency response and safety management system). Tadić et al (2014); Macuzić et al (2016) suggested to evaluate resilience using a fuzzy approach. They suggest the following steps: (1) creating an organizational reference model and to identify the factors that contribute to resilience, (2) weighing the importance of these factors and processes using a fuzzy approach, (3) determining linguistic expressions to evaluate these factors, (4) calculating the resilience factors' values using a fuzzy approach and (5) ranking the organizational resilience factors.…”
Section: Measuring Organizational Resilience Based On Other Techniquesmentioning
confidence: 99%
“…In the literature, papers can be found which assume that the resilience assessment should be done on the level of organizational processes [13,14] with assets that can be influenced by managers in order to keep the measurement consistent over time. In this manner, industrial processes may be assessed from the perspective of the contributing factors of resilience [14]. A lot of events described with insufficient data may have an influence on resilience of critical processes in an organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this manner, organizational resilience corresponds to the maximum percentage change given in the worst-case level of performance [12] that an organization may withstand. Overall organizational resilience of an SME is based on assessment of verified potential factors of organizational resilience (ORPFs) [13,14] estimated by using fuzzy sets theory. Since it may be assumed that their value is not subject to change over a predefined period of time, ORPFs are analyzed as static variables.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations